Morphometric analysis of peripheral nerves in people with spinal cord injury - Aurora Messina; Mary P. Galea (Scientific Reports)
Abstract The morphology of peripheral nerves sampled at the time of nerve transfer surgery was directly assessed in participants within 15 months of their SCI. Fresh nerve samples were fixed in glutaraldehyde, processed and embedded in Araldite Epon. Light and electron microscopy was used to conduct a qualitative analysis of morphology and a quantitative morphometric analysis of axon, fibre and myelin areas and diameters and g-ratios. Over two-thirds of both donor and recipient nerves showed abnormalities that differed in appearance and aetiology. These included myelin thickening and folding (tomacula), demyelination, reduced density of large, myelinated axons, oedematous endoneurium, evidence of compression, and thickened epineurium and perineurium. Morphometric analysis showed differences in axon density and myelination in the sampled nerves, with substantial nerve fibre loss in teres minor and posterior axillary nerves, and increased myelin area in the other sampled nerves. Mean (SD) myelin area ranged from 26.23 (13.86) to 66.02 (32.14) µm2 in donor nerves, and from 54.58 (25.29) to 74.04 (31.72) µm2 in recipient nerves. The g-ratio was affected by the degree of myelin thickening and ranged from 0.6 to 0.7 to values below 0.25 in fibres where the myelin was thickened. The morphological findings show evidence of widespread peripheral nerve pathology after spinal cord injury. The loss of nerve fibres in teres minor and posterior axillary nerves may be related to compression. Myelin abnormalities are probably associated with loss of neural traffic after injury and may be reversible.